PENGARUH ORIENTASI PASAR, INOVASI, ORIENTASI KEWIRAUSAHAAN TERHADAP KEUNGGULAN BERSAING DAN KINERJA PEMASARAN (Effects of Market Orientation, Innovation, Entrepreneurship Orientation on Competitive Advantage and Marketing Performance) - Alihusna Alihusna; Alida Palilati; Juharsah Juharsah (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study are: 1) to determine the effect of market orientation on competitive advantage in DKP SMEs under Wakatobi Regency.2) to determine the effect of innovation on competitive advantage 3) to determine the effect of entrepreneurial orientation on competitive advantage. 4) to determine the effect of market orientation on marketing performance 5) to determine the effect of innovation on marketing performance 6) to determine the effect of entrepreneurial orientation on marketing performance. 7) to determine the effect of competitive advantage on marketing performance.The research design used is quantitative research. The study population was all members of the SME group. The sample used in this study was a member of 28 groups taken by simple random members of each group of 100 people. Data was collected through questionnaires, and then the data generated were obtained by structural equation modeling analysis, using the help of AMOS software version 24.0.The results showed that: Market orientation has a significant effect on competitive advantage, Innovation has a significant effect on competitive advantage, Entrepreneurial orientation has a significant effect on competitive advantage, Market orientation has no significant effect on competitive advantage, Innovation has no significant effect on competitive advantage, Entrepreneurial Orientation has no significant effect on competitive advantage, and competitive advantage does not significantly influence competitive advantage.Keywords: market orientation, innovation, entrepreneurial orientation, competitive advantage & marketing performance